Gut microbiome skin axis in the development of atopic dermatitis - Hitham Abduarhman Alghamdi; Ahmed Behieldin; Sherif Edris (Journal of the Pakistan Medical Association, 2021)
Abstract Atopic dermatitis (AD) is the main focus of this review which mostly starts with children in early life. Beside the etiological factors like environmental, dietary or medical exposures, Gut-skin axis microbiome studies have an impact to investigate and to understand the relation between the gut microbiome and changes to the skin microbiom and some skin diseases resulting like AD. Infants start forming their microbiome in early life and some researches suggest that this time have a crucial role in development of AD. Balanced bacterial composition is important to maintain healthy skin as the gut microbiome dysbiosis may result in dramatic shifting in the skin microbiome that gives better chance for some bacteria such as Staphylococcus aureus to over prevail which has been reported to contribute in AD development. Among several factors, immunological activity has a strong relation to microbiome changed composition and development of AD. Continuous....